Pengaruh Relationship Marketing dan Kepercayaan Pelanggan terhadap Loyalitas Konsumen dengan Keputusan Pembelian sebagao Variabel Intervenig: - Chelly Widyantriana; Henny Welsa; Putri Dwi Cahyani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of Relationship Marketing and Customer Trust on Consumer Loyalty with Purchase Decisions as Intervening Variables (a case study on Aqua Mineral Water in Indonesia). The population used in this study were consumers who had consumed Aqua Mineral Water. The sample in this study were 126 respondents using the Non-Probability Sampling technique with the Purposive Sampling approach. Sampling with a certain balance, with the criteria of respondents who have consumed Aqua Mineral Water. Data was taken using a questionnaire via the Google form, after the questionnaire results were collected, the data was tabulated using MS Exel and analyzed using SPSS version 24. The results of this study indicate that Relationship Marketing has a significant positive effect on Consumer Loyalty. Customer Trust has a significant positive effect on Consumer Loyalty. Purchase decision has a significant positive effect on consumer loyalty. The Effect of Relationship Marketing on Consumer Loyalty through Purchasing Decisions as an Accepted Intervening Variable. The Effect of Customer Trust on Consumer Loyalty through Purchasing Decisions as an Accepted Intervening Variable. Keywords : Relationship Marketing; Customer trust; Buying decision ; Costumer Loyalty